Real world outcomes in KRAS G12C mutation positive non-small cell lung cancer. (August 2020) - Cui, Wanyuan; Franchini, Fanny; Alexander, Marliese; Officer, Ann; Wong, Hui-Li; IJzerman, Maarten; Desai, Jayesh; Solomon, Benjamin J.
Highlights: All patients with KRAS G12C mutant NSCLC were active or ex-smokers. 33 % KRAS mutant versus 40 % KRAS wildtype NSCLC developed brain metastases (p = 0.17). 40 % KRAS G12C versus 41 % other KRAS mutant NSCLC developed brain metastases (p = 0.74) Overall survival was similar between KRAS mutant and KRAS wildtype NSCLC (p = 0.54). Overall survival was similar between KRAS G12C and other KRAS mutant NSCLC (p = 0.39). Abstract: Background: KRAS mutations are found in 20–30 % of non-small cell lung cancers (NSCLC) and were traditionally considered undruggable. KRAS G12C mutation confers sensitivity to KRAS G12C covalent inhibitors, however its prognostic impact remains unclear. This study assesses the frequency, clinical features, prevalence of brain metastases and outcomes in KRAS G12C NSCLC in a real-world setting. Methods: Patients enrolled in the prospective Thoracic Malignancies Cohort (TMC) between July 2012 to October 2019 with recurrent/metastatic non-squamous NSCLC, available KRAS results, and without EGFR/ALK/ROS1 gene aberrations, were selected. Data was extracted from TMC and patient records. Clinicopathologic features, treatment and overall survival (OS) was compared for KRAS wildtype ( KRAS WT ) and KRAS mutated ( KRAS mut ); and KRAS G12C and other ( KRAS other ) mutations. Results: Of 1386 NSCLC patients, 1040 were excluded: non-metastatic/recurrent (526); unknown KRAS status (356); ALK/EGFR/ROS1 positive (154); duplicate (4). Of 346 patients analysed, 144 (42 %) were KRAS mut, of whom 65 (45 %) were KRAS G12C . All patients with KRAS G12C were active or ex-smokers, compared to 92 % of KRAS other and 83 % of KRAS WT . The prevalence of brain metastases during follow-up was similar between KRAS mut and KRAS WT (33 % vs 40 %, p = 0.17), and KRAS G12C and KRAS other (40 % vs 41 %, p = 0.74). The proportion of patients receiving one or multiple lines of systemic therapy was comparable. OS was similar between KRAS mut and KRAS WT (p = 0.54), and KRAS G12C and KRAS other (p = 0.39). Conclusion: Patients with KRAS mut and KRAS WT, and KRAS G12C and KRAS other NSCLC have comparable clinical features, treatment and survival. While not prognostic, KRAS G12C may be an important predictive biomarker as promising KRAS G12C covalent inhibitors continue to be developed.